Firm Performance Based on Sustainability Report and Intellectual Capital - Dina Septriana; Lisa Martiah Nila Puspita (Master of Accounting Universitas Trunojoyo Madura, 2024)
Environmental damage and global warming are being discussed throughout the world. Disclosure of sustainability reports plays a role in assessing the company’s environmental, economic, and social responsibilities due to corporate activities. This study intends to establish whether Intellectual Capital and sustainability reports affect financial performance. Secondary data was obtained from the Indonesian Stock Exchange, emphasizing JIIlisted companies. The method of data processing involves the utilization of EViews 9. The study’s findings indicate that sustainability reports have negligible implications for firm performance. The presence of intellectual capital has been found to have a favorable influence on the organizations financial performance. Intellectual capital has been found to improve the financial success of firms. Therefore, this research can help stakeholders observe opportunities for long-term firm performance and determine the direction of policies that will be implemented to realize company goals.